Esforço mental e suscetibilidade à interferência na recuperação da memória episódica - Alves, Marcus Vinicius Costa [UNIFESP] (2018)
Forgetting is the inability to retrieve information that could be retrieved before. The Interference Theory suggests that information tends to dispute its existence when learned by individuals, so forgetting would be justified by the dispute of information prior to the entry of the target memories (Proactive Interference) and subsequent to that entry (Retroactive Interference). Currently, there is a hypothesis that memory consolidation is impaired by the introduction of tasks demanding cognitive effort during the time it is occurring. The present study aimed to investigate whether the loss of information related to cognitive effort could be explained by interference in memory consolidation or because of the limited ability of individuals' mental resources to control interfering stimuli. To measure cognitive effort we registered pupil dilation. Experiment 1 (N - 20) replicated our previous study that demonstrated a possible non - existence of the interfering effect on memory consolidation. Experiment 2 (N - 22) tested how the tasks performed at the initial moment of memory consolidation could influence recall by interfering with more labile memories, but this effect was not fund. In Experiment 3 (N - 30) the participants performed tasks over a longer period of time, testing whether loss of information would come from RI in memory consolidation or cognitive overload, indicating the possibility of the second hypothesis being more correct. Finally, in Experiment 4 (N - 45), we tested in groups how different tasks interfere in consolidation causing a cognitive overload. The results of our study indicate that there is no interfering effect of cognitive effort on memory consolidation, but rather a proactive and retroactive effect on the retrieval of information that people have for evocation.